Unraveling the shift in bacterial communities profile grown in sediments co-contaminated with chlorolignin waste of pulp-paper mill by metagenomics approach - Kumar, Vineet; Ameen, Fuad; Verma, Pradeep (Frontiers in Microbiology, 2024)
Pulp-paper mills (PPMs) are known for consistently generating a wide variety of pollutants, that are often unidentified and highly resistant to environmental degradation. The current study aims to investigate the changes in the indigenous bacterial communities profile grown in the sediment co-contaminated with organic and inorganic pollutants discharged from the PPMs. The two sediment samples, designated PPS-1 and PPS-2, were collected from two different sites. Physico-chemical characterization of PPS-1 and PPS-2 revealed the presence of heavy metals (mg kg−1) like Cu (0.009–0.01), Ni (0.005–0.002), Mn (0.078–0.056), Cr (0.015–0.009), Pb (0.008–0.006), Zn (0.225–0.086), Fe (2.124–0.764), Al (3.477–22.277), and Ti (99.792–45.012) along with high content of chlorophenol, and lignin. The comparative analysis of organic pollutants in sediment samples using gas chromatography–mass spectrometry (GC–MS) revealed the presence of major highly refractory compounds, such as stigmasterol, β-sitosterol, hexadecanoic acid, octadecanoic acid; 2,4-di-tert-butylphenol; heptacosane; dimethyl phthalate; hexachlorobenzene; 1-decanol,2-hexyl; furane 2,5-dimethyl, etc in sediment samples which are reported as a potential toxic compounds. Simultaneously, high-throughput sequencing targeting the V3–V4 hypervariable region of the 16S rRNA genes, resulted in the identification of 1,249 and 1,345 operational taxonomic units (OTUs) derived from a total of 115,665 and 119,386 sequences read, in PPS-1 and PPS-2, respectively. Analysis of rarefaction curves indicated a diversity in OTU abundance between PPS-1 (1,249 OTUs) and PPS-2 (1,345 OTUs). Furthermore, taxonomic assignment of metagenomics sequence data showed that Proteobacteria (55.40%; 56.30%), Bacteoidetes (11.30%; 12.20%), and Planctomycetes (5.40%; 4.70%) were the most abundant phyla; Alphproteobacteria (20.50%; 23.50%), Betaproteobacteria (16.00%; 12.30%), and Gammaproteobacteria were the most recorded classes in PPS-1 and PPS-2, respectively. At the genus level, Thiobacillus (7.60%; 4.50%) was the most abundant genera grown in sediment samples. The results indicate significant differences in both the diversity and relative abundance of taxa in the bacterial communities associated with PPS-2 when compared to PPS-1. This study unveils key insights into contaminant characteristics and shifts in bacterial communities within contaminated environments. It highlights the potential for developing efficient bioremediation techniques to restore ecological balance in pulp-paper mill waste-polluted areas, stressing the importance of identifying a significant percentage of unclassified genera and species to explore novel genes.